Sequential study of liver biopsy in thalassaemia. Issue 10 (October 1980) - Masera, G; Jean, G; Conter, V; Terzoli, S; Mauri, R A; Cazzaniga, M
Abstract : Liver biopsies were performed in 47 thalassaemic children. 33 of them had laboratory findings that suggested chronic hepatitis; the other 14 patients, without such signs, underwent liver biopsies during splenectomy. Nine patients showed a more or less pronounced fibrosis, 26 showed chronic persistent hepatitis, and 12 had histological evidence of chronic aggressive hepatitis. The last 12 patients who had been treated with corticosteroids, and 9 other patients who showed a worsening of their liver function tests, underwent sequential biopsy. We suggest that chronic liver disease in thalassaemic children can produce inflammatory infiltration even without biochemical or clinical sign of chronic hepatitis, that it can progress towards cirrhosis even in patients with chronic persistent hepatitis, and that there appears to be no benefit in giving corticosteroids.